Tinjauan Pemutusan Hubungan Kerja Sepihak dalam Perspektif Regulasi Hukum Ketenagakerjaan (Studi Kasus: Putusan Nomor 101/PDT.SUS-PHI/2019/PNSMR) - Koniardy, Delvina; Lie, Gunardi (Universitas Ekasakti, 2023)
Layoffs or what is usually called one-sided termination of employment is something that is still problematic to this day and causes the emergence of industrial relations disputes, as happened in Decision Number 101/Pdt.Sus-PHI/2019/PNSmr where industrial relations disputes occurred between PT. NALA PALMA CADUDASA with 6 people from the Public Relations Team and Senambah Village Verification Team. There was a misunderstanding regarding the definition of a partnership relationship and working relationship between the two parties which led to disputes when the relationship was terminated. The research method used in this research is normative juridical with a case approach. A partnership relationship is a relationship based on a partnership agreement, while an employment relationship is a relationship based on a work agreement. The position between parties in a partnership relationship and an employment relationship is also different. In a partnership relationship, each party has the same position in terms of rights and obligations, whereas in an employment relationship the positions of the entrepreneur and employee are superior and subordinate. However, when a partnership relationship has elements of a work relationship, the partnership relationship turns into a work relationship.